Acoustical modelling of the surface sources – IV. Interpolation model, axisymmetric problem - BRAŃSKI, A. (Archives of Acoustics, 1996)
In the paper, the quadratic shape function were applied to construct an interpolation model of a plane axisymmetric source. Optimizing the least squares distance between the exact directivity function and directivity of the model, an optimal interpolation model was found. The optimal model was considered as a function of the shape of the vibration velocity, wave number and the place of the driving surface in the baffle. An optimal model was compared to other interpolation models, namely regular and irregular ones.